Ca2+, Fe3+ co-crosslinked tannic acid-bridged sodium alginate gel membrane for organic solvent nanofiltration - Li, Haike; Kong, Zhiyun; Zhang, Huan; Wang, Xiaolei; Xie, Yaohua; Zhao, Xingqing; Hong, Yidan (Separation and purification technology, 2024)
[Display omitted] •Preparation of gel membrane by bridging TA to SA.•The double network enhanced the solvent resistance of the gel membrane.•Gel membrane had higher porosity and mechanical properties.•Gel membrane had high dye anti-fouling and self-cleaning ability. It is necessary to prepare a nanofiltration membrane with high permeation flux that can be used in the field of organic solvents. Gel membranes have a high solvent permeation flux, but their chained macromolecular structure is often unstable. In this study, tannic acid-bridged sodium alginate (TAx-Ca/FeSA) organic solvent nanofiltration (OSN) membranes were prepared by the phase transition method using aqueous Ca2+ and Fe3+ solutions as cross-linking agents. TA can interact with SA through hydrogen bonding hydrophobic bonding and other interactions to form an interpenetrating three-dimensional network structure. Compared with Ca/FeSA membrane, the average pore size of TA0.125-Ca/FeSA membrane was reduced from 1.03 nm to 0.74 nm, and the porosity was increased from 47.62 to 59.2 %. In addition, the TA0.125-Ca/FeSA membrane has the characteristics of a negative charge, super hydrophilicity, and high mechanical properties, exhibits a high permeation flux of 48.97 L·m−2·h−1·bar−1 with a rejection of 96.25 % for Congo red ethanol solution, has excellent solvent resistance, stain resistance, and self-cleaning ability. The TA0.125-Ca/FeSA membrane was demonstrated to have great potential for application in the fields of purification and solvent recovery.